Acupuncture and Sciatica - Ali Ismail Qasim; Seyed Javad Mojtabavi (Kufa Journal for Nursing Sciences)
Abstract: Traditional Chinese Acupuncture has a history of over 3,000 years. The World Health Organization recommends the use of acupuncture treatment for many diseases including headaches, migraine, low back pain, sciatica and others. The prevalence of sciatica is about 3% - 5%, and equally common in men and women. In most patients, the prognosis is good, but up to 30% will have pain for one year or longer